O letramento do aluno surdo na escola regular: perspectivas e desafios - Sena , Fábia Sousa de (2017)
In this paper, we discuss about deaf student’s literacy and some of results achieved from the performance of intervention project accomplished in a public school of full-time education that presents bilingual teaching proposal for the deaf people in João Pessoa city. This research was based on the theoretical methodological presuppositions of qualitative research from ethnographic nature. We observed in this study how the deaf students' literacy is performed and the challenges faced by them in the achievement and participation of the activities proposal in their second language. To get information, we used as instruments, classroom observations and questions to managers, deaf students and Portuguese teachers that work in elementary education. In order to base our paper, we take as reference the literary books like, Dorziat (1999, 2012), Kleiman (1998), Lodi e Lacerda (2014), Pereira (2000), Santana (2007), Schmiedt (2006), Skiliar (1998), Soares (2002), Quadros (2006), Stumpf (2009) and others who concern literacy involving deaf, considering the Brazilian Sign Language as natural language of the deaf community, which through it, people can effectively communicate with the world and develop cognitively. The research results got through observations, questionnaires and workshops indicate that activities involving textual genres, TICs and multimodality in the classroom have a great acceptance by deaf people contributing to the literacy process of the person mentioned, we also realize the need of instigate the discussion strengthening the commitment of the school to everybody, allowing ground for a diferent look wich glimpse in our society changes in the existing models.